Framing Analysis – Possibilities of Use in Studies of Media Discourse on Higher Education - Rzyska, Aleksandra (Przegląd Badań Edukacyjnych (Educational Studies Review), 2023)
This article presents the basic assumptions and tools characteristic of framing analysis – a perspective of reconstructing schemas of interpretation (frames) in public communication. The potential of framing in research on discourse, especially in analyses of media discourse and higher education, has been described, along with an example of designing an analytical process of media framing of the university in the context of the current reform of higher education in Poland. Introducing the essentials of framing and reflection on the processes of assigning meanings are in line with the goal of promoting conscious participation in public discourse and shaping the reality of higher education and the contemporary university.